High Sensitivity Quantitative Allele Specific RHOA G17V PCR for Diagnosis, Staging and Minimal Residual Disease Assessment in Angioimmunoblastic T-Cell Lymphoma - Sidorova, Yu.V.; Chernova, N.G.; Kovrigina, A.M.; Sinitsyna, M.N.; Moiseeva, T.N.; Al- Radi, L.S.; Aleksenko, M.Yu; Glinshchikova, O.A.; Smirnova, S.Yu.; Ryzhikova, N.V.; Nikulina, E.E.; Zakharko, E.I.; et al. (Journal of Hematology Research, 2018)
Angioimmunoblastic T-cell lymphoma (AITL) is a T-cell lymphoma, characterized by abundant polymorphocellular infiltrate of lymph nodes with the small number of tumor CD4+ Tfh-cells. AITL could often be misdiagnosed as reactive processes and other lymphomas, including Hodgkin’s lymphoma and diffuse large B-cell lymphoma (DLBCL). We used quantitative allele-specific PCR with LNA (locked nucleotide acid) modified primers (qAS-PCR-LNA) for RHOA G17V mutation assay. Sensitivity of determination (0.02%) was sufficient for minimal residual disease (MRD) monitoring and evaluation of tumor cell number in different tissues. Method proposed demonstrated sensitivity superior to histology and PCR-based clonality determination. RHOA G17V mutation in lymph nodes was detected in 53% (32 of 62) patients with AITL. In control group (n-110) we have revealed RHOA G17V mutation in 3 patients with Hodgkin’s lymphoma (HL) and 1 patient with diffuse large B-cell lymphoma (DLBCL). Three patients with HL had clonal CD4+ T-lymphocytes population with aberrant immunophenotype in blood and clonal rearrangements of TCRG and/or TCRB genes in lymph nodes. We have shown that RHOA G17V can be used as a screening marker for patients with lymphadenopathy to exclude AITL or PTCL NOS. The persistence of tumor cells with RHOA G17V mutation was shown in most patients (12 of 16 -75%) with AITL after the induction chemotherapy and during the maintenance therapy (5 of 7 - 71.4%). Therefore qAS-PCR-LNA can be enrolled into standard protocols for management of patients with AITL to assess the effectiveness and the duration of antitumor therapy.